Histórias em quadrinhos na sociedade contemporânea: lazer, produção e obtenção de conhecimento na leitura das revistas de super-heróis - Rubem Borges Teixeira Ramos (2008)
This dissertation aims to observe and analyze the Marvel and DC super-heroes comic books and their readers, presenting some considerations regarding the reading process of these comic books, as an instrument for information disclosure and also as an instrument for knowledge construction, which allows the readers to realize, interact and rebuild the world where they live, through the process of opinion making and analysis. Starting from a theoretical focus, in which is presented a definition of comic books, its nature as a mass media product and an introduction to the Marvel and DC super-heroes and other charactersuniverses, the analysis will identify the elements inside these super heroes comic books used by the readers in their lives, in order to stand out the possible reasons and purposes that carry them to continue this specific kind of reading, not only as kids or teens, but also through theiradult lives.